"Thinking too much" and "worrying too much": Ghanaian women's accounts of their health problems - Avotri, Yaa Joyce (My University, 1997)
Women's voices are usually absent in the literature on women's health in developing countries. We know little about women's own concerns about their health, the ways in which they understand the problems they experience, how they cope and what changes they think would help to improve their health. The information on women in developing countries is typically provided by academics, health professionals, non-governmental organizations and policy makers. We do not know whether this captures the views of women themselves. Moreover, explanations of women's health often rely on biomedical and cultural/behavioural models and we do not know whether these reflect women's own approaches to understanding their health.
The research reported here documents the health problems and concerns of Ghanaian women. Using the concept of the social production of illness, the research also aimed to determine whether women traced their health problems to the social and material conditions under which they lived. The data are drawn from semi-structured interviews with 75 women in Kpando, a community in south-eastern Ghana. The data show that, when asked to talk about their health, women do not dwell on reproductive health issues. Rather, they emphasize "worrying too much" and "thinking too much", as well as a range of physical health problems. In their explanations of health problems women talked about their roles in social reproduction and production and about the links between their social relationships and their health. In order to perform their roles and avoid disrupting household organization, women relied on short term coping mechanisms, especially painkillers. In the longer term they called for an improvement in the situation of women through social structural changes - better access to education, jobs and credit. The research findings prompt questions about commonly held assumptions about women in the developing world and they illustrate the value of listening to the voice of women.
Keywords: Sociology; Sociology